Discovery, synthesis and biochemical profiling of purine-2, 6-dione derivatives as inhibitors of the human poly(A)-selective ribonuclease Caf1. Issue 19 (1st October 2015) - Jadhav, Gopal P.; Kaur, Ishwinder; Maryati, Maryati; Airhihen, Blessing; Fischer, Peter M.; Winkler, G. Sebastiaan
Graphical abstract: Abstract: Eukaryotic mRNA contains a 3′ poly(A) tail, which plays important roles in the regulation of mRNA stability and translation. Well-characterized enzymes involved in the shortening of the poly(A) tail include the multi-subunit Ccr4-Not deadenylase, which contains the Caf1 (Pop2) and Ccr4 catalytic components, and poly(A)-specific ribonuclease (PARN). Two Mg 2+ ions present in the active sites of these ribonucleases are required for RNA cleavage. Here, we report the discovery, synthesis and biochemical profiling of purine-2, 6-dione derivatives as (sub)micromolar inhibitors of Caf1.